GRANDES TAXONES DE FITOBENTOS Y SU RELACIÓN CON LA HIDROLOGÍA, FÍSICA Y QUÍMICA DE PEQUEÑOS RÍOS ANDINOS - Rivera Rondón, Carlos Alberto; Unidad de Ecología y Sistemática, Departamento de Biología, Facultad de Ciencias. Pontificia Universidad Javeriana, Bogotá (2004)
In 16 sampling points, which were located in 14 streams of the middle and high basin of the Bogotá River (2.617 - 2.988 m), we analyzed some physical, chemical and hydrological variables and the benthic algae community (taxonomic classes). By means of Principal Component Analysis, we concluded that the rivers respond to a basin area gradient and mineralization gradient. The streams are of the acidic order 1-4, and their flow rates are lower than 3.7 m3 s-1. The total nitrogen and total  phosphorus concentrations are lower than 7 mg l-1 and 1.4 mg l-1,  respectively. The benthic community is dominated by diatoms,  cyanobacteria and green algae. The basin area and mineralization gradients determine the dominant and co-dominant benthic algae class per stream.